HAART slows progression to anal cancer in HIV-infected MSM. (28th January 2015) - Duncan, Katrina C.; Chan, Keith J.; Chiu, Connie G.; Montaner, Julio S.G.; Coldman, Andy J.; Cescon, Angela; Au-Yeung, Christopher G.; Wiseman, Sam M.; Hogg, Robert S.; Press, Natasha M.
<x xml:space="preserve">Abstract</x> Objective: Antiretrovirals do not prevent anal intraepithelial neoplasia. However, the influence of antiretrovirals in the natural history of invasive anal cancer is less clear. The objective is to investigate the impact of antiretrovirals in the time to the development of anal cancer in HIV-positive MSM. Design: A retrospective analysis of cases of anal cancer in a cohort of HIV-positive MSM receiving antiretrovirals between 1988 and 2008. Methods: Time from first CD4+ cell count or HIV RNA viral load test to anal cancer diagnosis was analysed using Cox regression and Kaplan–Meier curves. Anal cancer cases treated in the era prior to HAART (<1996) were compared with those treated later (1996–2008). Results: Anal cancer cases (n = 37) were compared with a cohort of 1654 HIV-positive MSM on antiretrovirals. Antiretrovirals were started in the pre-HAART era by 70% of cancer cases, and median CD4+ cell count nadir was 70 cells/μl (10–130). Time to development of anal cancer was shorter for cases treated during the pre-HAART era [adjusted hazard ratio (AHR) 3.04, 95% confidence interval (95% CI) 1.48–6.24, P = 0.002], with a CD4+ cell count nadir less than 100 cells/μl (AHR 2.21, 95% CI 1.06–4.62, P = 0.035) and longer duration of CD4+ cell count less than 100 cells/μl (AHR 1.33, 95% CI 1.11–1.58, P = 0.002). Conclusion: Results show that severe immunosuppression and starting therapy pre-HAART are associated with an increased risk of anal cancer. HIV-positive MSM initiating antiretrovirals during the HAART era (1996–2008) had a longer time to the development of anal cancer than those treated pre-HAART. Our results suggest that early use of HAART may delay progression to anal cancer.